Pathogenesis-related proteins response in citronella grass (Cymbopogon nardus) infected by Curvularia andropogonis - ROFIATUN SOLEKHA; M. AINUL MAHBUBILLAH; M. BADRUT TAMAM; FADHILATUSTSANI SOFIALANA; ALIFIA HAYA AS-SYIFA; ACHMAD DJAZULI; HERY PURNOBASUKI (Society for Indonesian Biodiversity, 2025)
Abstract. Solekha R, Mahbubillah MA, Tamam MB, Sofialana F, As-Syifa AH, Djazuli A, Purnobasuki H. 2025. Pathogenesis-related proteins response in citronella grass (Cymbopogon nardus) infected by Curvularia andropogonis. Biodiversitas 26: 5485-5494. The development and growth of citronella grass (Cymbopogon nardus) are often hindered by Curvularia andropogonis fungal infection, which causes leaf disease. One key approach is to identify the expression of Pathogenesis-Related (PR)-17 and PKS type III defense proteins in citronella after C. andropogonis infection, serving as a model for counterattacking fungal infection. This study aimed to (i) determine chalcone synthase enzyme activity in C. nardus against C. andropogonis infection, (ii) identify the PR-17 response of C. nardus leaves, and (iii) identify the metabolic variations of flavonoid derivatives of C. nardus leaves. High-Performance Liquid Chromatography was carried out to analyze the enzyme activity. Protein identification was performed using sodium dodecyl sulfate. The variation of secondary metabolites was measured using Gas Chromatography-Mass Spectrometry. The results indicated that the enzyme CHS activity in infected C. nardus leaves had increased significantly compared to healthy leaves. PR-17, PR-2, and PR-3 were only expressed in C. nardus infected with C. andropogonis. Profile of flavonoid-derived metabolites in C. nardus infected with C. andropogonis changed significantly, involving seven flavonoid-derived metabolites. The activation of CHS, accompanied by elevated expression of defense-related proteins and increased levels of flavonoid derivatives, creates a synergistic defense strategy in infected C. nardus. These responses strengthen the plant immunity, restrict fungal colonization, and enhance overall resistance, making them important indicators of plant-pathogen interactions.